Collection of Malay unverified social media posts using crowdsourcing / Ahmad Ruzaini Awang Ahmad - Awang Ahmad, Ahmad Ruzaini (2016)
Facebook is a social media platform that enables Facebook user to update status, pictures, videos and many more. As user can share and update their status or post on their Facebook newsfeed, therefore the information shared or posted is unreliable. The information shared or posted may be unverified and can lead to slander and misunderstanding. Therefore, this application will collect unverified Malay post using crowdsourcing. Crowds or Facebook users can send the unverified Malay post in their Facebook newsfeed through this application in the Facebook. Admin then will extract the keywords in the post using word repetition technique and save it into the database. Then script for the automated matching post to its categories will be run to store the new submitted posts to its type of category based on the list of keywords generated by the script. By that, this application may able to help researchers, academicians or any other interested parties by providing chart of what types of category most of user shared. Thus, the researchers or academicians able to do more research or focus on the type of category that user shared and by having this information, the authorities and professionals in the related field can be involved to help solve the problem of unverified information being shared. This project is using Rapid Application Development (RAD) to design and develop the Facebook app and the web application.